Household Recycling In Reducing Residual Total Solid Waste at Sandakan Disposal Site - Abdul Hair Beddu Asis; Mohammad Tahir Mapa (2020)
The increase in population of a country will be directly proportional to the high domestic waste generation at the landfill. Various methods and technologies have been introduced to manage the growing amount of waste. But the results are only temporary. One of the best approaches to managing waste is to reduce the amount of waste at the source level of the waste. Thus, this study was conducted to identify the recycling practices of households around the administrative district of Sandakan Municipal Council (MPS) in reducing the amount of waste disposed at Sandakan landfill. This study uses questionnaire as the data collection method. In addition, interviews and observations were also conducted to support the findings of this study. The findings show that households in the MPS region have contributed to the reduction of waste by recycling by 3.82% of the total waste produced at the landfill. Households contributing to the reduction of waste at landfill are small, but recycling culture has begun to be practiced among households. This demonstrates the positive development towards reducing the amount of waste at the landfill thus further extending the life span of the landfill.